TEACHERS ENGAGEMENT AND STUDENT INTERACTIONS FOR SUPPORTTING 21st CENTURY SKILLS - Alex , Dr. Velankanni; Ye, Dr. Yan (Migration Letters, 2023)
This is an exciting and challenging time for teacher educators. The nature of teaching is changing. To transform themselves into exemplary educator preparation institutions, many programs are becoming more entrepreneurial, recognizing new opportunities and making changes required to respond to the needs of 21st century learners. Engage prospective teachers in creating instruction aligned with their state’s curriculum standards, effectively interpreting assessment results, responding to students’ learning needs, and cultivating a passion for learning that will support students for a lifetime, and Meet the demands of the global economy by exemplifying, and embedding in instruction, the mastery of 21st century skills such as critical thinking, problem-solving, communication, collaboration and creativity and innovation. This includes the application of technology to support more robust instructional methods and understanding the relationship between content, pedagogy, and technology through dissemination of Technological Pedagogical Content Knowledge (TPCK) theory and research. The purpose of this paper is to create the foundation for ongoing dialogue around how 21st century knowledge and skills could be appropriately embedded in educator preparation, and to guide the development of resources and services to support educator programs. Today as never before, meeting our society’s challenges demands educational excellence. Reinvigorating the economy, achieving energy independence with alternative technologies and green jobs, and strengthening our health care system require a skilled populace that is ready for the critical challenges we face. There is widespread consensus, however, that our education systems are failing to adequately prepare all students with the essential 21st century knowledge and skills necessary to succeed in life, career and citizenship. The benefactors are teachers, administrators.